MAKNA RUANG JALAN DI KOTA LAMA KUPANG MENURUT PENGGUNA RUANG PEDAGANG INFORMAL DAN FORMAL (The significance of the space of kota lama Kupang street according to the informal and formal street vendors) - Mberu, Yuliana Bhara; Purbadi, Yohanes Djarot (ARTEKS Jurnal Teknik Arsitektur, 2018)
The Space at Soekarno Street and Siliwangi Sreet in the Kota Lama Kupang area has existed since the establishment of Kupang city.  Since then, this space has developed into a trading area and played important role as economic and  social interaction instrument in the life of the people.   The long-lasting activities and usage of the space by users, especially by the informal and formal traders indicate how they give meaning to the space.  Finding the meaning of street space of Kota Lama will be benefitial in encouraging development sustainability and in contributing thoughts to the parties responsible for the continuing life at Kota Lama Kupang. The aim of this research was to find out the meanings of street space of Soekarno and Siliwangi Streets at Kota Lama Kupang and  the underlying terms according to the space users of informal and formal sellers. The research employed qualitative approach with inductive analysis method. The informants were 24 informal sellers and four formal sellers who have been at the space for more than 15 years.  The finding of the research was the depth knowledge about the meaning of space according to the informal and formal sellers and the concept underlying their existence. There were two concepts of meanings of the space found, namely living survival and local life unity (community). Both concepts were supported by six themes, namely theme of economy, kinship, togetherness, bonding with the place, gender and annual event. It was concluded that the meaning of Space Street at Kota Lama Kupang was categorized as local meaning. Keywords: meaning of street space, space users, kota lama, Kupang